Empowerment of Smallholder Women Farmers through Self-Help Groups in South-West India (Indian Journal of Extension Education, 2021)
Though women act as the backbone of world agricultural workforce most of them are economically backward. But, self help group (SHG) movement made some tangible changes in empowering rural women in India. The study was carried out among 120 SHG women farmers and 60 non-SHG women farmers of south west India to analyze the impact of SHGs in empowering rural farm women. Results showed most of SHG women farmers as highly empowered and their economic empowerment found to be prominent compared to control group. However, empowerment score of non-SHG women farmers showed strong correlation with some social and technological indicators. Major factors that favoured sustainable high performance of SHGs were; heterogeneity of the group, proximity of the women’s households, income generation and extension contact. The study confirmed that acquisition of some autonomy by women in social participation and economic decision-making have contributed to overcome many constraints that hamper their overall empowerment.